Analysis of the Implementation of PSAK 1 Concerning the Presentation of Financial Statements in Construction Companies in Indonesia - Harjuno, Dharu; Vitarani, Dina; Raditiningsih, Sri; Gusliana Mais, Rimi (SINOMIKA Journal: Publikasi Ilmiah Bidang Ekonomi dan Akuntansi, 2025)
This study examines the implementation of PSAK 1 in the financial statements of PT Adhi Karya (Persero) Tbk. It focuses on analyzing the structure and classification of key financial statement elements, including assets, liabilities, revenues, and expenses. Using a qualitative descriptive approach, this research employs content analysis of the company’s annual reports and financial statements. The findings indicate that PT Adhi Karya’s financial statements comply with PSAK 1 standards, including transparency, relevance, and comparability of financial data. However, challenges remain in managing high operating expenses, particularly in short-term liabilities, which require enhanced liquidity management strategies. The study recommends improving the disclosure of operating expenses, liquidity strategies, and the impact of long-term financing in the financial statement notes to support more informed decision-making by stakeholders.